2021
DOI: 10.3390/fishes6040084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Partial Soybean Replacement by Shrimp By-Products on the Productive and Economic Performances in African Catfish (Clarias lazera) Diets

Abstract: The present study was carried out to evaluate the effects of partial replacement of soybean with shrimp by-products (SBp) in African catfish (Clarias lazera) diets on productive (growth, digestibility, body composition, dressing yield, blood parameters, immunity) and economic performances. Therefore, 750 fingerlings (~20.0 g) were distributed into five groups of 150 fingerlings/group with three replicates (n = 50) per group. Group 1 was fed a basal diet, while G2 and G3 were fed diets containing 25% SBp (autoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Besides, shrimp by-product (SBp) has been identified as a possible animal protein source by increasing shrimp production from captures and farms. The study showed that replacing soybean with SBp (especially 50% acid-treated) positively influenced the productive and economic performances of African Catfish (Clarias lazera) [3]. Plant extracts achieved a success in the aquaculture industry as dietary supplements in promoting growth and immunity.…”
Section: Fish Nutrition and Physiologymentioning
confidence: 99%
“…Besides, shrimp by-product (SBp) has been identified as a possible animal protein source by increasing shrimp production from captures and farms. The study showed that replacing soybean with SBp (especially 50% acid-treated) positively influenced the productive and economic performances of African Catfish (Clarias lazera) [3]. Plant extracts achieved a success in the aquaculture industry as dietary supplements in promoting growth and immunity.…”
Section: Fish Nutrition and Physiologymentioning
confidence: 99%
“…According to Qin et al (2022), soybean meal contains high protein with a balanced amino acid composition. Shrimp feed for Litopenaeus vannamei contains the highest composition of vegetable protein (30-35%) (Abu-Alya et al 2021). It is one of the main determinants of the quality of aquaculture production (Nunes et al 2022).…”
Section: Introductionmentioning
confidence: 99%